Trends in the pricing and reimbursement of new anticancer drugs in South Korea: an analysis of listed anticancer drugs during the past three years. (4th May 2021) - Kim, Sungju; Kim, Jinhong; Cho, Hyunyoung; Lee, Kyungmin; Ryu, Chiyoung; Lee, Jong Hyuk
ABSTRACT: Objective : This study aimed to examine patient accessibility to new anticancer drugs including reimbursement coverage, time to listing, and listing price during the recent 3 years after the introduction of alternative pricing and reimbursement pathways in South Korea. Methods : Anticancer drugs were selected for analysis from the new drugs reviewed from January 2017 to March 2020. Descriptive statistics were used to present the levels of the listing prices. Pearson's correlation analysis was used to analyze the relationship between the list price in comparison to the External Reference Price(ERP) and the time to listing. Results : Thirty-two anticancer drugs were included in analysis. The average time to listing for these drugs was 36.7 months. The ratio of the listing price in comparison with Average Adjusted Price from seven reference countries was from 12.6% to 90.2%. Pearson's correlation coefficient for the correlation between the ratio of the listing price to the ERP and the time to listing was −0.37 and was statistically significant (p = 0.035). Conclusions : Policies that relate to the scope of reimbursement, time to reimbursement, and list price should be able to equally reflect patient accessibility and national health insurance finances, as well as the impact on industry as a whole.